Evaluating the efficacy of anti-Müllerian hormone as a predictor of ovarian reserve and fertility treatment success - Holy, Mirza Farzana; Jahan, Esmat; Al-Maruf, Abdullah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Ovarian reserve assessment is crucial for predicting fertility treatment outcomes, with Anti-Müllerian Hormone (AMH) emerging as a key biomarker. This study aimed to evaluate the efficacy of AMH as a predictor of ovarian reserve and its correlation with fertility treatment success among women in Bangladesh. Methods: This retrospective study analyzed medical records of 100 women aged 20-40 years who underwent fertility treatment at a specialized clinic in Bangladesh over five years. AMH levels were measured using VIDAS and ovarian reserve was assessed via antral follicle count (AFC) using transvaginal ultrasound. The correlation between AMH levels, AFC, oocytes retrieved and clinical pregnancy rates was analyzed using Pearson's correlation coefficient with statistical software SPSS 26. Results: The study found a significant positive correlation between AMH levels and AFC, with 80% of women with high AMH levels also having a high AFC. Additionally, women with high AMH levels had higher oocyte retrieval rates and clinical pregnancy rates (70%) compared to those with medium (50%) and low AMH levels (29.4%). The nearly equal distribution of clinical pregnancy outcomes (49% achieving pregnancy) highlighted the varied success of fertility treatments in this population. Conclusions: AMH is a valuable predictor of ovarian reserve and fertility treatment outcomes, particularly when combined with AFC and other patient-specific factors. This study supports the use of AMH in clinical settings to enhance individualized fertility treatment strategies, potentially improving success rates.